The Islamic Legal Perspective on A’Matoang in the Marriage Process (Exploring Agreements within the Monromonro Utara Community, Jeneponto Regency) - Abdul Aziz Khotibul Umam; Muh Zaitun Ardi; Samsidar Jamaluddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The research delves into the A’matoang customary tradition within marriage from the perspective of Islamic law. Conducted as a field study, it directly engages with subjects to gather pertinent data. Employing a juridical-empirical approach, the study incorporates data collection methods such as observation, interviews, documentation, and subject-object identification. In accordance with the Urf theory (Customary Tradition) in Islamic Law, the A’matoang tradition in marriage has long prevailed in the Jeneponto region. This tradition involves the bride's family visiting the groom's family, presenting various gifts as expressions of gratitude or reciprocation for the dowry given. From the Islamic legal standpoint, A’matoang is deemed an Urf or customary tradition consistently practiced. The Islamic legal perspective emphasizes that this tradition is an established Urf or customary practice, considered valid as it aligns with Islamic teachings and avoids elements of polytheism. The implications of this research underline the importance of preserving the A’matoang Tradition while prioritizing well-being and adherence to Islamic teachings. If this cultural practice potentially brings significant harm to its participants, abandonment is deemed advisable. Ideally, the post-marriage A’matoang Tradition should not merely signify respect or a gift to the groom's family in response to the dowry, but also serve as a prayer for Allah’s blessings in fostering a harmonious marital life (sakinah, mawadah, warahmah).